Effect of heart ischemia and administration route on biodistribution and transduction efficiency of AAV9 vectors. (22nd December 2019) - García‐Olloqui, Paula; Rodriguez‐Madoz, Juan Roberto; Di Scala, Marianna; Abizanda, Gloria; Vales, África; Olagüe, Cristina; Iglesias‐García, Olalla; Larequi, Eduardo; Aguado‐Alvaro, Laura Pilar; Ruiz‐Villalba, Adrián; Prosper, Felipe; Gonzalez‐Aseguinolaza, Gloria; et al.
Abstract: Adeno‐associated viruses (AAV) have become one of the most promising tools for gene transfer in clinics. Among all the serotypes, AAV9 has been described as the most efficient for cardiac transduction. In order to achieve optimal therapeutic delivery in heart disease, we have explored AAV9 transduction efficiency in an infarcted heart using different routes of administration and promoters, including a cardiac‐specific one. AAV9 vectors carrying luciferase or green fluorescence protein under the control of the ubiquitous elongation‐factor‐1‐alpha or the cardiac‐specific troponin‐T (TnT) promoters were administered by intramyocardial or intravenous injection, either in healthy or myocardial‐infarcted mice. The transduction efficacy and specificity, the time‐course expression, and the safety of each vector were tested. High transgene expression levels were found in the heart, but not in the liver, of mice receiving AAV‐TnT, which was significantly higher after intramyocardial injection regardless of ischemia‐induction. On the contrary, high hepatic transgene expression levels were detected with the elongation‐factor‐1‐alpha‐promoter, independently of the administration route and heart damage. Moreover, tissue‐specific green fluorescence protein expression was found in cardiomyocytes with the TnT vector, whereas minimal cardiac expression was detected with the ubiquitous one. Interestingly, we found that myocardial infarction greatly increased the transcriptional activity of AAV genomes. Our findings show that the use of cardiac promoters allows for specific and stable cardiac gene expression, which is optimal and robust when intramyocardially injected. Furthermore, our data indicate that the pathological status of the tissue can alter the transcriptional activity of AAV genomes, an aspect that should be carefully evaluated for clinical applications.